Studi Komparatif Transformasi Produksi Animasi 3D Berbasis AIGC dan Animasi 3D Tradisional dalam Konten Bertema Kucing - Kristiyawanto Kristiyawanto; S. Rouli Manalu (Rekam, 2026)
Comparative Study of AIGC-Based 3D Animation Production Transformation versus Traditional 3D Animation in Cat Content. This study conducts a comparative analysis of the transformation of 3D animation production, by contrasting AI-Generated Content (AIGC)-based workflows with traditional 3D animation in cat-themed content. Employing qualitative content analysis and Christian Fuchs’ framework of capital circulation, the research compares The Garfield Movie as a representative of traditional animation with the YouTube channel Cartoon Tube HD as an example of AIGC-driven production. Findings reveal that AIGC dramatically reduces production costs from approximately USD 60 million to merely USD 20–50 per video, shortens production time from months or years to only 1–3 hours, and transforms the labor structure from hundreds of animators to only 1–3 prompt engineers. The efficiency of surplus value  reaches 1,900% for AIGC, significantly higher than the 328.33% of traditional animation. AIGC further enables sustainable global distribution via social media with recurring monthly revenues of USD 200–1,000. The study concludes that while AIGC substantially enhances production efficiency, it intensifies the commodification of media by incorporating audience free labor. Despite its economic advantages, this transformation raises serious ethical concerns regarding the exploitation of creative labor and content homogenization. The research recommends further studies on the long-term cultural and ethical implications of AIGC for the digital animation industry.